Bagaimana Literasi dan Perilaku Keuangan pada Generasi Milenial? - Mega Noerman Ningtyas; Novi Lailiyul Wafiroh (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2021)
The rise of illegal investment in Indonesia has made the OJK more vigorously conducting financial literacy education to the public. It is hoped that victims of illegal investment can be minimized in such a way that they can increase inclusion and public trust in financial services institutions and products in Indonesia. Research shows that individuals who have a high level of financial literacy will tend to do good financial planning such as: saving, making budgeting, paying debts on time and investing. This study aims to measure the level of financial literacy and how it affects financial behavior in millennial generations. Millennial generation here is the generation born between 1980-1994. This generation has unique characteristics where it is very concerned about social life and tends to be more consumptive than the previous generation. This is what makes it difficult for this generation to wisely manage finances. The results of this study indicate that financial literacy shows a significant positive effect on financial behavior. From this research it can be said that differences in knowledge will lead to differences in attitudes and behavior.